ANALISIS KINERJA SIMPANG BERSINYAL DAN BERLENGAN EMPAT (STUDI KASUS SIMPANG BPKP, BANDA ACEH) - Sofyan M. Saleh; Noer Fadhly; Ruhdi Faisal (JURNAL TEKNIK SIPIL, 2012)
Abstract: BPKP intersection is located in Banda Aceh City. This intersection was modified from three approaches between T.P. Nyak Makam Street and T. Iskandar Street, to be four approaches intersection.  The new approaches is connected T.P. Nyak Makam Street to B. Aceh – Medan National road after finishing Santan Bridge. The objective of this study is to analyze the performance of four approaches junction with traffic signal. Video Camera was installed in the data collection then analyze with Indonesian Highway Capacity Manual (IHCM, 1997) and the result would be come out in graphs and tables. The result showed that at peak hour and the highest flow are from the North approaceh, South approaches, east approach, and West approache consecutively; 810 pcu/hour, 571 pcu/hour, 797 pcu/hour, and 870 pcu/hour. Meanwhile the capacity for the existing condtion for those four approaches are consecutively; 596 pcu/hr, 766 pcu/hr, 770 pcu/hr, and 557 pcu/hr. From these data of the existing condition then can be found that the average degree of saturation (DS) is 1,18 and average delay is 402,6 sec/pcu, with cyclus time 89 second. After adjusting the geometric of junction, the performance is getting better with increase in capacity all approaches namely; the North approaceh tobe 1093 pcu/hr, South approaches 771 pcu/hr, East approach 1076 pcu/hr, and West approache 1174 pcu/hr. The average DS for all approach become lower to 0,74, and the average delays to be 24,4 sec/pcu. After predicting 5 years later with average traffic grouth of 17,5% per year, so DS will be 1,66, it means that need to be evaluated.Keywords : Flow, capacity, degree of saturation, delay, cyclus time.Abstrak: Simpang BPKP terletak di Kota Banda Aceh, sebelumnya merupakan simpang berlengan tiga antara jalan T. P. Nyak Makam dengan jalan T. Iskandar. Setelah dibangunnya Jembatan Santan yang merupakan terusan jalan T. P. Nyak Makam menuju jalan Nasional B. Aceh – Medan di Desa Meunasah Manyang Aceh Besar, maka Simpang BPKP menjadi simpang berlengan empat. Penelitian ini bertujuan untuk menganalisa kinerja simpang berlengan empat yang diatur dengan sinyal lalu lintas. Pengumpulan data  dilakukan dengan menggunakan kamera video yang kemudian diolah menggunakan metode MKJI 1997 dan hasil yang didapat dalam bentuk tabel dan grafik. Hasil perhitungan jam puncak dengan arus tertinggi diperoleh pada lengan Utara, Selatan, Timur dan Barat masing-masing sebesar 810 smp/jam, 571 smp/jam, 797 smp/jam dan 870 smp/jam. Nilai kapasitas kondisi eksisting pada lengan Utara, Selatan, Timur dan Barat masing-masing sebesar 596 smp/jam, 766 smp/jam, 770 smp/jam dan 557 smp/jam. Nilai derajat kejenuhan rata-rata pada kondisi eksisting sebesar 1,18. Nilai tundaan rata-rata sebesar 402,6 det/smp. Waktu siklus eksisting yang disesuaikan sebesar 89 detik. Setelah dilakukan analisis dengan perubahan geometrik, kinerja simpang menjadi lebih baik ditandai dengan nilai kapasitas pada lengan Utara, Selatan, Timur dan Barat masing-masing sebesar 1093 smp/jam, 771 smp/jam, 1076 smp/jam dan 1174 smp/jam. Nilai derajat kejenuhan pada lengan Utara, Selatan, Timur dan Barat masing-masing sebesar 0,74. Nilai tundaan rata-rata sebesar 24,4 det/smp. Apabila diprediksi pertumbuhan kendaraan pertahun 17,5 %, maka untuk 5 tahun mendatang diprediksi simpang dengan perubahan geometrik memiliki nilai DS sebesar 1,66 untuk setiap lengan-lengan simpang.Kata kunci : arus lalu lintas, kapasitas, derajat kejenuhan, tundaan, waktu siklus.